Love me - Nelson, Zed (Roma : Contrasto, 2009)
This text explores the insidious power of the global beauty industry and our collective insecurity, vanity and fear of ageing. It negotiates the boundaries of art and documentary, reflecting a world we have created in which there are enormous social, psychological and economic rewards and penalties attached to the way we look.
boek
Keywords: Nelson, Zed